EXPLORING THE RELATIONSHIP BETWEEN SMEs FINANCING AND ENTREPRENEURS’ PERCEPTIONS ON THE DEVELOPMENT OF THE HOSPITALITY INDUSTRY IN SYLHET - Sarker, Md. Sajadul Islam; Chowdhury, Md. Asraful Islam (International Journal of Small and Medium Enterprises, 2023)
By serving and gratifying clients, the hospitality business has a significant potential to stimulate economic growth and to increase shareholder wealth. The study’s primary goal is to examine how SME financing has affected Bangladesh’s growing hotel sector. Growth in services and jobs are important SMHE development determinants. The theoretical model displays how the researcher has conceptualized the relationships between the study’s variables. We employed factor analysis, test of hypothesis, and descriptive analysis to conduct quantitative analysis for this paper using SPSS. In this work, both primary and secondary data have been utilized. Primary data collection will be done in the Sylhet districts (Sadar) utilizing standardized questionnaires that will concentrate on the borrower’s perspective of SME funding. Secondary data was gathered from academic journals, theoretical evaluations of SME foundations, papers, Bangladesh Bank magazine reviews, and BBS reports. A survey will be undertaken to obtain feedback from the owners or managers of various hotels, restaurants, and managed food services in the districts of Sylhet (Sadar). The study found a strong correlation between organizational behavior measures and SME finance. This study also poses the possibility that the Sylhet region’s hotel sector could improve its performance through smart SME financing. The study also suggested potential future uses of SME finance in hospitality firms in the Sylhet region. The framework includes the impact of SME financing on revenue, job growth, and their ‘customers. JEL Classification Codes: F62, F65, G21, G23.